MINIATURIZED ANTIPODAL VIVALDI ANTENNA BASED ON MAGNETODIELECTRIC MATERIALS - Stepanyan, Ararat H.; Haroyan, Hovhannes S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2022)
Miniaturization of antipodal Vivaldi antenna (AVA) based on high dielectric constant and magnetodielectric ferrite materials is studied. The basic parameters of antipodal Vivaldi antenna based on high dielectric and magnetodielectric materials (MDM) are compared. To miniaturize the size of the antenna by a higher factor, MDM ferrite with paremeters ε_r=μ_r=8 is used. The analysis shows that MDM based Vivaldi antenna surface is minimized by a factor of 4 compared to that of air-based Vivaldi antenna. The sizes of AVA are 120 × 120 × 1 (mm).